External Anatomical Shapes Reconstruction from Turntable Image Sequences using a Single off-the-shelf Camera - Azevedo, Teresa; R. S. Tavares, João Manuel; Vaz, Mário A. P. (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2008)
Three-dimensional (3D) human body reconstruction and modeling from two-dimensional (2D) images is a topic of great interest and research but still remains a difficult problem to solve. Volumetric based methods are commonly used to solve this type of problem. With those methods, from a turntable image sequence of an object, a 3D model can be built. The final goal of the work presented in this paper is to reconstruct all-round 3D models of external anatomical shapes with good accuracy and photorealistic appearance, using a single off-the-shelf camera and a volumetric method.